Rift Valley fever - an emerging threat to livestock trade and food security in the Horn of Africa: A review - Bonnet, P.; Tibbo, Markos; Workalemahu, A.; Gau, M. (Ethiopian Society of Animal Production, 2002)
Rift Valley Fever (RVF), an insect-borne viral zoonotic disease caused by a member of the Phlebovirus genus of the family Bunyaviridae, was first recognised in the Rift Valley of Kenya in the early 1930s. Since then, several epidemics of RVF have occurred in northern, southern and eastern Africa becoming a continental problem. The epidemics that occurred in Egypt in 1977-78 and recent human and livestock cases in Yemen and Saudi Arabia (in September 1000) indicated the potential for the disease to spread to other inter-tropical regions of the world outside African continent. An embargo on livestock export by Gulf countries has brought in food insecurity in the East African countries due to indirect socio-economic mechanisms and impact of the ban on pastoralists household economy. Though food insecurity in the Horn of Africa is a longstanding problem, the recent ban imposed on eight countries, which are not yet recovered from the effects of recent droughts has further exacerbated the situation. Bertveen September and December 2000, livestock export dropped by 92% in Somalia. According to FSAUIFEWS (2001), the estimated total loss of income at the Somali owner/producer level (including livestock originated from eastern Ethiopia), reached 20-30 millions of USD. This figure does not include the reduced government revenue from livestock trade taxes. In Somalia, about 80% of foreign exchange earned from livestock exports are used to import basic food items and other commodities. The effect of livestock export ban was further compounded due to the decrease in imported commodities. This review emphasises on epidemiology and risk of RVF, and its impact on the future of the livestock sector and pastoralists household economy in the Horn of Africa; underscores the consequences on food security; analyses the current situation in a region already with multifaceted crises viewed against international experience.